Methodological theoretical model for creative action: A form of creation for a world in metamorphosis - Castro Torres, Fernando Andrés (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The methodological theoretical model for creative action is a structure that takes shape from participant observation, in-depth interviews and focus groups carried out with students of the Creative Thinking course and that allowed contrasting the entire theoretical framework built in the research. It is a triadic model that is supported by sensitive, intelligible and reflective knowledge to explore from the creative ethos the opportunities that the contemporary subject has to become and create and that becomes a new teaching formula for the construction of knowledge in a world in metamorphosis.